5G and beyond networks - Ruiz, Silvia; Ahmadi, Hamed; Gardaševi?, Gordana; Haddad, Yoram; Katzis, Konstantinos; Grazioso, Paolo; Petrini, Valeria; Reichman, Arie; Özdemir, Mehmet Kemal; Velez, Fernando; Paulo, Rui; Fortes, Sergio; et al. (Elsevier, 2021)
This chapter investigates the Network Layer aspects that will characterize the merger of the cellular paradigm and the IoT architectures, in the context of the evolution towards 5G-and-beyond, including some promising emerging services as Unmanned Aerial Vehicles or Base Stations, and V2X communications.
Keywords: 5G; Cloud Radio Access Network; IoT; Network Function Virtualization; Network Layer; New Radio; Radio Resource Management; Software Defined Network; Spectrum Management